Disparities in Income Distribution among Algerian Families During The period from 1988 to 2022 - GHERDAINE, Houssam; CHEBOUROU, Salim (Journal of Ecohumanism, 2025)
This research paper aims to identify the magnitude and degree of inequality in income distribution among the different segments of Algerian society during the period 1988–2022. This is achieved through studying and analyzing the evolution of primary income, disposable income, as well as trends in the distribution of consumer expenditure among Algerian households. The analysis is based on field surveys related to consumer expenditure and living standards of Algerian households for the years 1988, 1995, 2000, 2005, 2011, and 2022. The study also attempts to measure deviations in income distribution by calculating the Gini coefficient, the Kuznets coefficient, and income dispersion ratios among different social groups in order to assess the degree of inequality.The results indicate that the process of income distribution among Algerian households witnessed some improvement during the study period; however, it did not reach the level of equity in distribution.